(untitled) (Ustozlar uchun, 2026)
Translating idioms, metaphors, and humor across cultures remains one of the most intricate and debated challenges within Translation Studies. Unlike literal language, these expressive forms are deeply rooted in cultural context, collective experience, and shared systems of meaning, making direct equivalence between languages difficult—if not impossible—to achieve. Idioms often carry figurative meanings that cannot be deduced from their individual components, while metaphors rely on culturally specific associations and conceptual mappings. Humor, in particular, presents an additional layer of complexity, as it frequently depends on wordplay, phonetic similarities, timing, and culturally bound references that may lose their effect when transferred into another linguistic and cultural framework.